Pemberdayaan Perempuan Kelompok Usaha Bersama (Kub) Sedesa Kaya Batik Motif Daun Semangka di Kampung Dayun Kabupaten Siak - Fitrianingsih, Ayu; Resdati, Resdati; Yusuf, Yusmar; Risdayati, Risdayati (Peneliti.net, 2026)
This study aims to analyze women's empowerment through the Sedesakaya Joint Business Group (KUB) in the activity of making watermelon leaf batik motifs in Dayun Village, Siak Regency. The approach used is descriptive qualitative with data collection methods through observation, in-depth interviews, and documentation. The subjects in this study were 7 informants, 4 informants were members and heads of batik, 1 informant was the head of KUB, 1 informant was a batik buyer, and 1 informant was the head of Dayun Village. This empowerment process also faced obstacles such as the lack of regeneration of young members, limited time and dual roles of women, and unfavorable weather and work environment conditions. The empowerment that occurred was not only economic, but also social and cultural, which changed the power relations and identities of women in the local community. These findings were analyzed using Michel Foucault's perspective on power and knowledge, which explains that the practice of batik has become a medium of resistance and social transformation for women in Dayun Village. The results of the study indicate that KUB Sedesakaya plays a major role in improving women's skills, income, and economic independence. Empowerment is carried out through batik training, group work division, and expanding market access.